"Agent provocateur": Heinz Felfe as British spy. (13th September 2016) - Hechelhammer, Bodo
Abstract: In 1961, the staffer Heinz Felfe (1918–2008) of the Federal Intelligence Service of Germany, the "Bundesnachrichtendienst" (BND), was arrested under the accusation of spying for the Soviet Union. Over a period of 10 years, the former chief inspector, National Socialist German Worker's Party member, SS-Obersturmführer in the Sicherheitsdienst of the Reichsführer-SS and staffer at Reichssicherheitshauptamt worked for the BND and its predecessor organization "Organization Gehlen, " in his last capacity as a senior officer in the BND Branch in charge of counter intelligence/Soviet Union. But in fact, he spied for 10 years for the Soviet secret service "Komitet Gossudarstwennoi Besopasnosti" (KGB), against the foreign intelligence service of West Germany. Heinz Felfe later justified his double life. He explained that in the late 1940s and beginning of the 1950s, he passed a watershed, when his political understanding and judgement changed him from an anti-Communist to a Communist. He described precisely the period beginning with his release from British war captivity in the autumn of 1946 and his hiring as Soviet agent in the autumn of 1951. During this time, he was a student at the Rheinische Friedrich-Wilhelms University in Bonn, where he founded a Marxist student society, became a member of the "Communist Party of Germany" (KPD) and traveled often to the Soviet Occupation Zone. Heinz Felfe did not change his global political beliefs and remained a staunch Communist, whose spying for Moscow was merely the logical consequence of that developmental process. In fact, however, Heinz Felfe also worked for almost three years for the British secret service as well; his mission was to spy on Communist activities at Bonn University and the KPD in the British Occupation Zone, as well as later in North Rhine-Westphalia, in West Germany.